Penerapan Kahoot! dalam Pembelajaran Bahasa Arab di SMA Muhammadiyah 1 Nganjuk - Hafana, Najwa; Setyabudi, M. Arif (Lembaga Yasin AlSys, 2025)
Low student interest and understanding of Arabic language lessons present major challenges in secondary education, necessitating innovative learning media that can enhance student engagement and motivation. This study aims to describe the implementation of the interactive learning media Kahoot! in Arabic language instruction at SMA Muhammadiyah 1 Nganjuk. Employing a qualitative case study design, data were collected through observations, in-depth interviews, and documentation involving teachers and eleventh-grade students. The findings reveal that Kahoot! is used as an evaluation and reinforcement tool following conventional instruction. Supporting factors include school policies endorsing digital device use and the availability of Wi-Fi networks. Conversely, obstacles encountered involve limited internet connectivity and unequal access to devices among students. The study concludes that Kahoot! effectively increases student participation and motivation in Arabic language learning. The implications highlight the need to strengthen digital infrastructure and enhance teacher capacity to optimize the use of technology-based interactive learning media across diverse educational contexts.